Uma Proposta de utilização de um software educacional para o ensino de poliedros - Batista, Carolina Cordeiro [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This paper presents an educational proposal to use an educational software for the teaching of mathematics, following in the conduct of activities, the main aspects of sociocultural theory of Vygotsky. For this, it chose the Poly educational software, with which were developed teaching and learning activities for the polyhedra content provided in the São Paulo State Mathematics curriculum for the 7th year of elementary school. The objectives of this pedagogical proposal are to stimulate situations of social interaction among students and between students and the teacher, using an educational software as a mediator instrument and present a different way of using digital technology in math classes, aiming production of mathematical knowledge

Neste trabalho, é apresentada uma proposta pedagógica relativa à utilização de um software educacional para o ensino de matemática, fundamentada na teoria sociocultural de Vygotsky. Para isso, foi escolhido o software educacional Poly, com o qual foram desenvolvidas atividades de ensino e aprendizagem referentes ao conteúdo de Poliedros previsto no Currículo de Matemática do Estado de São Paulo para o 7º ano do Ensino Fundamental II. Os objetivos desta proposta pedagógica são: estimular situações de interação social entre os alunos e entre alunos e o professor, tendo um software educacional como intrumento mediador e apresentar uma forma diferenciada de uso de tecnologias digitais em aulas de matemática, visando à produção do conhecimento matemático
Keywords: Matemática - Estudo e ensino; Ensino auxiliado por computador; Análise de interação em educação; Mathematics Study and teaching